ISOLASI DAN IDENTIFIKASI BAKTERI PENGHASIL IAA DAN PELARUT FOSFAT DARI RHIZOSFER TANAMAN KELAPA SAWIT - Hilwa Walida; Fitra Syawal Harahap; Miranda Hasibuan; Febri Fitri Yanti (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
The potential of various genera and species of rhizosphere bacteria is well known. This study aims to determine the diversity and physiological characteristics of the rhizosphere bacterial isolates of oil palm plants at PTPN III Aek Nabara Labuhanbatu North Sumatra. This research was conducted in July 2018 to October 2018 in laboratory of STIPER Labuhanbatu. This research was conducted by isolating bacteria from the root rhizosphere of oil palm plants, characterizing the morphology and physiology of isolates by phosphate dissolution test and indole acetic acid production test. Furthermore, the data was analyzed descriptively. Based on the isolation results obtained 10 bacterial isolates with different macroscopic and microscopic morphological characteristics with the largest amount of dissolved phosphate produced by isolate R05 (0.211 mg / l) and the largest amount of IAA produced by isolate R04 (0.097 mg / l). Isolates R05 and R04 have the potential to be further tested.